Impact behavior and finite element prediction of the compression after impact strength of foam/vinylester-glass composite sandwiches. (September 2014) - Gordon, Sebastien; Boukhili, Rachid; Merah, Nesar
This paper presents the impact and compression after impact behavior of PVC foam cored /E-glass reinforced/vinylester sandwiches used in a four-seat amphibian aircraft. The impact damage was sorted in three categories: barely visible impact damage; visible impact damage; and clearly visible impact damage. It was observed that when increasing impact energy, the extension of the damage from barely visible impact damage to visible impact damage corresponds to a significantly high rate of energy absorption as depicted by the absorbed energy/impact energy ratio. Sandwich coupons were modeled with the finite element analysis ANSYS software to predict the critical failure load in presence of damage zones equivalent to those observed experimentally. The finite element model predicts consistently the compression after impact strength of undamaged coupons and this result confirms the model used to represent the woven fabric by an equivalent cross-ply laminate model. However, the finite element overestimates the compression after impact strength of impacted ones. It is suggested that the induced out-of-plane displacements generate stress concentrations in the tip of cracks located at the borders of the damaged zone.